Comparative effects of acute and subacute lycopene administration on chromosomal aberrations induced by cisplatin in male rats - Sendao, Milena Cristina; Behling, Estela Beatriz; dos Santos, Raquel Alves; Greggi Antunes, Lusania Maria; Pires Bianchi, Maria de Lourdes (Elsevier B.V., 2006)
Lycopene is a natural carotenoid, free radical scavenger, and presents protective effects by inhibiting oxidative DNA damage. The objective of the current study was to investigate the cytogenetic effects of a single acute and four daily gavage administrations of lycopene, and to examine possible protective effects on chromosomal damage induced by the antitumor drug cisplatin (cDDP) in rat bone marrow cells. The animals were divided into treatment groups, with three lycopene doses in the acute treatment (2, 4, and 6 mg/kg b.w.), three lycopene doses in the subacute treatment (0.5, 1.0, and 1.5 mg/kg b.w.) with and without cDDP (5 mg/kg b.w. i.p.), and respective controls. The results indicated that lycopene is neither cytotoxic nor clastogenic when compared with the negative controls (P > 0.01). cDDP-treated animals submitted to acute and subacute treatments with different lycopene doses showed a significant reduction (p < 0.01) in the number of abnormal metaphases when compared with the animals treated only with cDDP. The protective effects of lycopene on cDDP-induced chromosomal damage may be attributed to its antioxidant activity. These results suggest that this carotenoid may prove useful in reducing some of the toxic effects associated with certain classes of chemotherapeutic agents. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: lycopene; chromosome aberrations; clastogenicity; cisplatin; anticlastogenicity